Forage suitability on native and introduced estival grasses during the year of implantation in the central semi-arid region: Forage suitability on native and introduced estival grasses during the year of implantation in the central semi-arid region (Veterinary Science, 2025)
The objective of this study was to evaluate the aboveground biomass production and nutritional quality of native and introduced summer forage species used in the semiarid Pampas region for improving forage supply and restoring degraded grasslands. The native summer grasses evaluated were two populations of Leptochloa crinita and one of Pappophorum caespitosum. The introduced grasses were: Eragrostis curvula, Panicum coloratum, Eragrostis superba, Tetrachne dregei, and Digitaria eriantha. The experimental design followed a completely randomized block design with three replicates, using 1.5 m² plots per species, each containing 12 plants spaced 50 cm apart. Differences between treatments were assessed using ANOVA, followed by Tukey’s test for mean comparison (p